Manaqib Writing in the Circle of the Tariqa Qadiriyya wa Naqsyabandiyyah: A Study on Muhammad Siddiq al-Salihi’s Nayl al-Amani - Widiyanto, Asfa (Heritage of Nusantara: International Journal of Religious Literature and Heritage, 2015)
The manaqib of ‘Abd al-Qadir al-Jilani is of particular importance in the circle of the Tariqa Qadiriyya wa Naqsyabandiyyah (TQN). Some leaders of the TQN have done their best to give a translation and explanation of this manaqib. For instance, Muhammad Siddiq al-Salihi composed a work titled Nayl al-amānī fī dhikr manaqib al-quṭb al-rabbānī sayyidinā al-shaykh ‘Abd al-Qādir al-Jīlanī. Another leader, Muslih ibn ‘Abd al-Rahman al-Maraqi, wrote a treatise titled al-Nūr al-burhānī fī tarjamat al-lujayn al-dānī fī dhikr nubdhah min manaqib al-shaykh ‘Abd al-Qādir al-Jīlanī. The TQN master Nawawi  Siddiq  al-Zarkashi  wrote  a  treatise  titled  Fuyuḍāt  al-rabbānī  fīkayfīyāt qirā’at manaqib sulṭān al-awliyā’ al-shaykh muḥyī al-dīn ‘Abd al-Qādir  al-Jīlanī.  This  paper  will  pay  particular  attention  to  the  Nayl  al-amani, since this work is relatively unknown in Indonesian academia. This book is written in standard Arabic, something which is nowadays rare in the Pesantren  and  tariqa  scholarship.  This  book  is  read  during  the  monthly communal  ritual  of  the  TQN  in  the  Pesantren  Manba’  al-Falah,  Dawe, Kudus,  Central  Java.  This  paper  strives  to  unravel  the  narratives  of hagiography in Nayl al-amani and also highlight the uniqueness of Nayl al-amani, most particularly in comparison with the two manaqib writings in the circle of the TQN in Central Java.